2017
DOI: 10.3390/land6020037
|View full text |Cite
|
Sign up to set email alerts
|

The Status of National Legal Frameworks for Valuing Compensation for Expropriated Land: An Analysis of Whether National Laws in 50 Countries/Regions across Asia, Africa, and Latin America Comply with International Standards on Compensation Valuation

Abstract: Abstract:The challenges associated with determining fair compensation for expropriated land have been extensively discussed and debated among scholars, practitioners, policymakers, and the public. However, to date, a comprehensive study of national-level compensation procedures established by law considering whether such procedures meet internationally recognized standards on compensation valuation has not been conducted. This article aims to bridge this gap by serving as a reference point and informing "fair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…Recent studies that examine expropriation and compensation procedures in 50 countries across Asia, Africa, and Latin America indicate that Nigeria's legal framework lags behind many of the other countries assessed in terms of its compliance with international standards on expropriation, compensation, and resettlement [2,13]. The governing law on expropriation in Nigeria is the Land Use Act (LUA), a law that has been highly criticized by NGOs, scholars, and the public [62].…”
Section: Comparative Legal Analysis Of Land Use Act With Internationamentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies that examine expropriation and compensation procedures in 50 countries across Asia, Africa, and Latin America indicate that Nigeria's legal framework lags behind many of the other countries assessed in terms of its compliance with international standards on expropriation, compensation, and resettlement [2,13]. The governing law on expropriation in Nigeria is the Land Use Act (LUA), a law that has been highly criticized by NGOs, scholars, and the public [62].…”
Section: Comparative Legal Analysis Of Land Use Act With Internationamentioning
confidence: 99%
“…The Local Government, if it is satisfied that an occupier or holder is entitled to possession, 2 In section 51, the LUA defines customary rights of occupancy as "the right of a person or community lawfully using or occupying land in accordance with customary law and includes a customary right of occupancy granted by a local government. "…”
Section: Comparative Legal Analysis Of Land Use Act With Internationamentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Keliang et al observed that out of 476 expropriation cases in China, a majority of the farmers were undercompensated [27]. According to the World Bank's Land and Governance Assessment Framework (LGAF), affected populations in Afghanistan, Brazil, Ethiopia, Nigeria, South Africa, South Sudan, and Tanzania were inadequately compensated for taken land [28]. Van Eerd and Banerjee found similar cases in Cambodia, Indonesia, Sri Lanka, and the Philippines [29].…”
Section: Literature Review Of Pareto Efficiency and Kaldor-hicks Critmentioning
confidence: 99%